2015
DOI: 10.2147/ppa.s81509
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood transplantation supplemented with the infusion of mesenchymal stem cell for an adolescent patient with severe aplastic anemia: a case report and review of literature

Abstract: Delayed hematopoietic recovery and increased rate of engraftment failure limit the use of umbilical cord blood transplantation (UCBT). We describe a case of severe aplastic anemia treated by UCBT combined with mesenchymal stem cells. Our case reveals that infusing mesenchymal stem cells early (about 40 days) after UCBT may promote hematopoietic recovery. This experience will guide clinical scientists, especially hematologists, to deal with similar situations and encourage them to widen this strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…UCBT has many advantages for treating WAS, as compared to other types of HSCT. For example, the acquisition of CB is easy, collection of CB is harmless, and the CB handling process, such as thawing, does not induce loss of cell proliferation[4,13-16]. In addition, CB transplantation showed a lower risk of acute and chronic GVHD than other transplantation strategies using a different cell source[17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UCBT has many advantages for treating WAS, as compared to other types of HSCT. For example, the acquisition of CB is easy, collection of CB is harmless, and the CB handling process, such as thawing, does not induce loss of cell proliferation[4,13-16]. In addition, CB transplantation showed a lower risk of acute and chronic GVHD than other transplantation strategies using a different cell source[17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of UCBT is that one can search and prepare umbilical cord blood on time without delay, and it has a low incidence and severity of graft versus host disease (GVHD)[3]. However, slow hematopoietic reconstruction and increasing probability of engraftment failure prevent widespread use of UCBT[4]. As a result, the patients who experience slow immune reconstitution are at high risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In the collective pool of patients that go to HCT, AA patients are at high risk of graft failure. There is evidence that supporting patients with HSCs in addition to MSCs will better support hematopoiesis and engraftment[ 59 - 61 ]. Initial case reports adding MSCs to transplantation were promising.…”
Section: Mscs For Immunomodulatory and Regenerative Therapymentioning
confidence: 99%
“…Initial case reports adding MSCs to transplantation were promising. Luan et al[ 61 ] reported a case of a patient with severe AA that underwent matched sibling cord blood transplant but had delayed engraftment; after giving a cord-blood-derived MSC infusion, the patient began to engraft and pancytopenia improved. Similarly, a report on 2 patients with severe AA who had graft failure after HCT were given second transplant from the same donor with addition of MSCs from a haploidentical maternal donor and they were able to engraft[ 59 ].…”
Section: Mscs For Immunomodulatory and Regenerative Therapymentioning
confidence: 99%
“…The patient experienced delayed hematopoietic recovery after transplantation, but hematopoietic function improved after the infusion of UC-MSCs. This suggests that early infusion of MSCs after HCT can promote the recovery of hematopoietic function [ 32 ]. Wu et al .…”
Section: Introductionmentioning
confidence: 99%